Konstruksi Hukum Kepemilikan Hak Cipta Atas Karya Artificial Inteliigence Dalam Perspektif Hukum Positif Indonesia - Ade Ahmad Maulana; Abraham Ferry Rosando (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rapid advancement of Artificial Intelligence (AI), particularly Generative Artificial Intelligence, has transformed the process of creating literary, artistic, and scientific works. AI's ability to autonomously generate various forms of creative output has raised significant legal questions regarding copyright protection and the ownership of AI-generated works. Indonesian Copyright Law, namely Law Number 28 of 2014 on Copyright, does not explicitly regulate works generated by AI, resulting in legal uncertainty concerning whether AI-generated output qualifies as a copyrightable work and who should be recognized as the copyright holder. This study aims to examine the legal status of AI-generated works as copyrightable subject matter and to formulate a framework for copyright ownership over AI-generated works within the perspective of Indonesian positive law. This research employs a normative legal method using statutory and conceptual approaches. Legal materials were collected through library research and analyzed qualitatively using a prescriptive legal analysis. The findings indicate that fully autonomous AI-generated works do not satisfy the legal requirement of authorship under Indonesian Copyright Law and therefore lack a legal basis for copyright protection. In contrast, AI-assisted works remain eligible for copyright protection provided that they reflect originality and substantial human intellectual contribution.